A Simple Neo-Keynesian Growth Model - Williamson, J. (Review of Economic Studies, 1970)
Journal Article A Simple Neo-Keynesian Growth Model Get access John Williamson John Williamson London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 2, April 1970, Pages 157–171, https://doi.org/10.2307/2296409 Published: 01 April 1970 Article history Received: 01 August 1968 Accepted: 01 May 1969 Published: 01 April 1970